An electrode for perfluoroalkyl and polyfluoroalkyl substance detection and its preparation method and application
Patent Information
- Application Number
- CN202311692140.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-08
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-12-08
AI Technical Summary
[0003]目前,高效液相色谱-质谱联用技术是检测PFAS的主要技术,然而采用该技术检测样品前需要富集样品中的待测物,前处理步骤复杂,而且检测限仅为10ng/L左右,具有检测限高,且仪器昂贵、仪器体积大无法用于实际环境的实时监测的缺点
[0016] The electrode for PFAS detection prepared in this invention exhibits a low detection limit and high detection sensitivity when used for the detection of target analytes. This is because the structure of the polymer surface cavity in polymer layer II matches the structure of the analyte, and the functional groups within the cavity interact with the analyte's F element via hydrogen bonding. Furthermore, when using the electrode for PFAS detection in this invention, PFAS detection can be performed using an amperometric method. Compared to the detection potential, the instrument can detect currents on a much lower order of magnitude, i.e., from nA to pA, resulting in a low detection limit for PFAS. In some embodiments of this invention, the detection limit for PFAS detection using the electrode described above can be as low as below 6.5 fmol/L, i.e., 6.5 × 10⁻⁶. -15 Below mol/L, therefore the mass concentration of LOD is as low as 3.498 × 10⁻⁶. -12 g/L or 0.003498ppt; and it can have a linear relationship in the range of 0.01-0.5pmol/L and 0.5pmol/L-5nmol/L, with a wide linear range.
Smart Images

Figure CN117871631B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical detection technology, specifically relating to an electrode for the detection of perfluoroalkyl and polyfluoroalkyl substances, its preparation method, and its application. Background Technology
[0002] Perfluoroalkyl and polyfluoroalkyl substances (PFAS) are widely used in the production of various products, including refrigerants, aqueous film-forming foam fire extinguishers, cosmetics, pesticides, coatings for paper and fiber materials, non-stick cookware, and electrical wires. During the production of these products, large amounts of PFAS are released into the environment. PFAS are chemically stable and difficult to decompose in nature, thus they are widely distributed in soil, air, and water. PFAS can damage the liver and immune system, and affect fetal development. Furthermore, long-term consumption of water contaminated with PFAS can lead to elevated cholesterol levels and thyroid disease, ultimately increasing the risk of cancer. Therefore, it is necessary to use appropriate methods to monitor the concentration of PFAS in the environment in real time.
[0003] Currently, high performance liquid chromatography-mass spectrometry (HPLC-MS) is the main technique for detecting PFAS. However, this technique requires enriching the analyte in the sample before detection, which involves complex pretreatment steps. Moreover, the detection limit is only about 10 ng / L, which has the disadvantages of high detection limit, expensive instrument, and large instrument size, making it unsuitable for real-time monitoring in actual environments. Summary of the Invention
[0004] The present invention aims to at least solve one of the technical problems existing in the prior art. To this end, the present invention proposes a method for preparing an electrode for the detection of perfluoroalkyl and polyfluoroalkyl substances. The prepared electrode can be used for electrochemical detection of PFAS by an electrochemical sensor, with a low detection limit, convenient portability, and the ability to realize real-time monitoring of PFAS.
[0005] The present invention also proposes an electrode for the detection of perfluoroalkyl and polyfluoroalkyl substances.
[0006] This invention also proposes an electrochemical sensor.
[0007] The present invention also proposes a method for detecting PFAS.
[0008] This invention also proposes applications of the aforementioned electrodes and electrochemical sensors.
[0009] In a first aspect, the present invention provides a method for preparing an electrode for the detection of perfluoroalkyl and polyfluoroalkyl substances, comprising the following steps:
[0010] S1, take a substrate with an intermediate electrode group I on its surface, wherein the intermediate electrode group I includes a working electrode preform I, and the working electrode preform I includes a metal conductive layer I and a carbon conductive layer I in contact with each other;
[0011] S2, the intermediate electrode group I is activated by oxygen plasma technology to obtain intermediate electrode group II, wherein the working electrode preform I is activated to form working electrode preform II;
[0012] S3, using raw materials containing template molecules and monomers, a polymer layer I is prepared on the surface of the working electrode preform II, the template molecules are removed to obtain polymer layer II, and thus the electrode for the detection of perfluoroalkyl and polyfluoroalkyl substances is obtained, wherein the template molecules include PFAS.
[0013] In some embodiments of the present invention, the template molecule is the same as the target analyte. The target analyte is a perfluoroalkyl or polyfluoroalkyl substance (PFAS).
[0014] Electrodes used for the detection of perfluoroalkyl and polyfluoroalkyl substances, abbreviated as: electrodes for PFAS detection.
[0015] The method for preparing an electrode for detecting perfluoroalkyl and polyfluoroalkyl substances according to embodiments of the present invention has at least the following beneficial effects:
[0016] The electrode for PFAS detection prepared in this invention exhibits a low detection limit and high detection sensitivity when used for the detection of target analytes. This is because the structure of the polymer surface cavity in polymer layer II matches the structure of the analyte, and the functional groups within the cavity interact with the analyte's F element via hydrogen bonding. Furthermore, when using the electrode for PFAS detection in this invention, PFAS detection can be performed using an amperometric method. Compared to the detection potential, the instrument can detect currents on a much lower order of magnitude, i.e., from nA to pA, resulting in a low detection limit for PFAS. In some embodiments of this invention, the detection limit for PFAS detection using the electrode described above can be as low as below 6.5 fmol / L, i.e., 6.5 × 10⁻⁶. -15 Below mol / L, therefore the mass concentration of LOD is as low as 3.498 × 10⁻⁶. -12 g / L or 0.003498ppt; and it can have a linear relationship in the range of 0.01-0.5pmol / L and 0.5pmol / L-5nmol / L, with a wide linear range.
[0017] It should be noted that in this article, the unit M represents mol / L, such as pM for pmol / L and nM for nmol / L.
[0018] In some embodiments of the present invention, the electrode used for detecting perfluoroalkyl and polyfluoroalkyl substances is a screen-printed electrode. A screen-printed electrode is abbreviated as SPE electrode.
[0019] Through the above embodiments, the SPE electrode in this invention is a miniaturized electrode with advantages such as small size, low cost, easy preparation, mass production capability, and easily tunable structure. It requires only a small amount of sample for detection and can be carried to different applications. Therefore, using the SPE electrode for electrochemical detection of PFAS via an electrochemical sensor enables rapid real-time monitoring of PFAS.
[0020] Furthermore, the SPE electrode in this invention avoids the disadvantages of high cost and cumbersome sample pretreatment, such as the lack of pretreatment required for solid-phase extraction. In this invention, the SPE electrode is used for PFAS detection, resulting in a low detection limit; in some embodiments, the detection limit can be below 6.5 fmol / L, i.e., 6.5 × 10⁻⁶. -15 The concentration is below mol / L, therefore the mass concentration of LOD is 3.498 × 10⁻⁶. -12 g / L or 0.003498 ppt; and exhibits a linear relationship within the ranges of 0.01-0.5 pmol / L and 0.5 pmol / L-5 nmol / L, demonstrating a wide linear range. Specifically, when the SPE electrode of this invention is used for the detection of target analytes, the structure of the polymer surface cavity matches the structure of the analyte, and the functional groups in the cavity interact with the F element of the analyte through hydrogen bonding, resulting in a low detection limit and high detection sensitivity for PFAS. Furthermore, when using the electrode for PFAS detection in this invention, galvanometry can be used for detection. Compared to the detection potential, the instrument can detect currents on a much lower order of magnitude, i.e., from nA to pA. Therefore, the SPE electrode of this invention has a low detection limit when used for PFAS detection.
[0021] Furthermore, the detection device involving the SPE electrode is portable and more suitable for real-time and accurate detection of pollutants, overcoming the limitation of high-performance liquid chromatography-mass spectrometry (HPLC-MS) in real-time PFAS detection. The SPE electrode in this invention can be connected to CHI, as well as portable workstations such as handheld workstations and USB flash drive workstations. It can be controlled via computer connection or wirelessly via mobile phones, iPads, and other devices, and can be carried to various scenarios. The electrochemical detection technologies that can be used can be implemented through the portable workstation. It has the advantages of small size and light weight, and can be carried to various scenarios to detect pollutants.
[0022] Screen printing technology allows for the mass production of screen-printed electrodes (SPEs) with high parallelism between each electrode, facilitating commercialization. SPE electrodes have low fabrication costs per piece, enabling mass production; the more SPE pieces produced in a batch, the lower the cost per piece. Furthermore, there is virtually no difference between individual SPE pieces within the same batch, and they can be stored for extended periods after fabrication.
[0023] In some embodiments of the present invention, the working electrode preform I includes a metal conductive layer I and a carbon conductive layer I sequentially stacked on the surface of the substrate.
[0024] In some embodiments of the present invention, in the working electrode preform I: the metal conductive layer I is disposed on the surface of the substrate.
[0025] In some embodiments of the present invention, in the working electrode preform I: a portion of the carbon conductive layer I is disposed on the surface of the metal conductive layer I, and another portion is disposed on the surface of the substrate; and / or, all of the carbon conductive layer I is disposed on the surface of the metal conductive layer I; and / or, all of the carbon conductive layer I is disposed on the surface of the substrate.
[0026] In some embodiments of the present invention, the intermediate electrode assembly I further includes an auxiliary electrode preform I and a reference electrode preform I, wherein the auxiliary electrode preform I includes a metal conductive layer II and a carbon conductive layer II stacked on the surface of the substrate, and the reference electrode preform I includes a metal conductive layer III disposed on the surface of the substrate.
[0027] In some embodiments of the present invention, the working electrode preform I, the auxiliary electrode preform I, and the reference electrode preform I are disposed at intervals on the same surface of the substrate. Optionally, the auxiliary electrode preform I, the working electrode preform I, and the reference electrode preform I are sequentially disposed on the same surface of the substrate.
[0028] In some embodiments of the present invention, the working electrode preform I further includes an insulating layer I disposed on the surface of the metal conductive layer I facing away from the substrate; the auxiliary electrode preform I further includes an insulating layer II disposed on the surface of the metal conductive layer II facing away from the substrate; the reference electrode preform I further includes an insulating layer III disposed in a portion of the surface of the metal conductive layer III facing away from the substrate. Optionally, the insulating layer I is adjacent to the carbon conductive layer I, and the insulating layer II is adjacent to the carbon conductive layer II. Optionally, the insulating layer III is disposed in the middle of the surface of the metal conductive layer III.
[0029] In some embodiments of the present invention, the metal conductive layer I, the metal conductive layer II, and the metal conductive layer III are not in contact with each other.
[0030] In some embodiments of the present invention, step S1 includes the following operations:
[0031] S1-1, the substrate surface includes adjacent region one and region two; metal conductive layer I, metal conductive layer II and metal conductive layer III are respectively prepared on the substrate surface;
[0032] A carbon conductive layer I is prepared on a portion of the surface of the metal conductive layer I, and / or a carbon conductive layer I is prepared on the surface of the substrate, wherein the carbon conductive layer I is in contact with the metal conductive layer I;
[0033] A carbon conductive layer II is prepared on a portion of the surface of the metal conductive layer II; thereby forming an electrode intermediate I on the substrate surface;
[0034] S1-2, then insulating layer I and insulating layer II are prepared on the surface of metal conductive layer I and the surface of metal conductive layer II, respectively; insulating layer III is prepared in the middle of the surface of metal conductive layer III; thus obtaining a substrate with intermediate electrode group I on the surface;
[0035] Wherein, one end of the surface of the metal conductive layer III without the insulating layer III and part or all of the carbon conductive layer I and part or all of the carbon conductive layer II are located in the first region; the insulating layer I, the insulating layer II and the insulating layer III are located in the second region.
[0036] In some embodiments of the present invention, in step S1-1, the surface of the metal conductive layer I facing away from the substrate includes region A, and the substrate surface includes region B adjacent to region A. A paste for preparing the carbon conductive layer I is applied to region A and / or region B to form the carbon conductive layer I. Region B is located within region I, and part or all of region A is located within region I. Optionally, region B does not include metal conductive layers I-III.
[0037] Through the above embodiments, the carbon conductive layer I is entirely located on the surface of the metal conductive layer I or the substrate surface, or a portion of the carbon conductive layer I is disposed on the surface of the metal conductive layer I and another portion is disposed on the substrate surface.
[0038] In some embodiments of the present invention, the carbon conductive layer I may be 1 / 10 to 4 / 5 of the area of the metal conductive layer I; and / or, the carbon conductive layer II may be 1 / 10 to 2 / 3 of the area of the metal conductive layer II.
[0039] In some embodiments of the present invention, the carbon conductive layer I includes a carbon conductive layer I-1 and a carbon conductive layer I-2, wherein the carbon conductive layer I-1 is located on the surface of the substrate, and the carbon conductive layer I-2 is located on the surface of the metal conductive layer I. Optionally, the area of the carbon conductive layer I-1 may be 1 / 10 to 1 / 5 of the area of the carbon conductive layer I, and may be 1 / 10 to 4 / 5.
[0040] In some embodiments of the present invention, the shape of the carbon conductive layer I-1 includes, but is not limited to, circles, polygons, etc.
[0041] In some embodiments of the present invention, in step S1-1, the metal conductive layer I, metal conductive layer II, and metal conductive layer III are disposed on the substrate surface in the same direction. Optionally, for example, the metal conductive layer I, metal conductive layer II, and metal conductive layer III are disposed on the substrate surface along the length direction of the substrate surface.
[0042] In some embodiments of the present invention, the substrate surface further includes region three, which is adjacent to region two; in the intermediate electrode group I, the surface of the metal conductive layer I further includes a blank region I without the carbon conductive layer I and the insulating layer I; the surface of the metal conductive layer II further includes a blank region II without the carbon conductive layer II and the insulating layer II; the surface of the metal conductive layer III includes blank regions III-1 and III-2 without the insulating layer III; the blank regions I, II, and III-2 are located within region three, and the blank region III-1 is located within region I. Optionally, the shape of the metal conductive layer III corresponding to the blank region III-1 is not limited, for example, it can be strip-shaped, circular, irregularly shaped, etc. Optionally, the area of region one can be 1 / 10 to 1 / 2 of the total area of the substrate surface; and / or, the area of region three can be 1 / 20 to 1 / 2 of the total area of the substrate surface.
[0043] In some embodiments of the present invention, region one and region three are not adjacent.
[0044] In some embodiments of the present invention, step S1-2 includes: applying insulating ink to region two of the surface of the electrode intermediate I obtained in step S1-1 that is away from the substrate, to form an insulating total layer containing insulating layer I, insulating layer II and insulating layer III.
[0045] In some embodiments of the present invention, the carbon conductive layer I, the carbon conductive layer II, and the blank region III-1 are located at the same end of the substrate surface.
[0046] In some embodiments of the present invention, the metal conductive layer I is located between the metal conductive layer II and the metal conductive layer III.
[0047] In some embodiments of the present invention, the metal conductive layer II includes a straight portion and a bent portion connected to the straight portion, the surface of the bent portion is provided with the carbon conductive layer II, the straight portion is not provided with the carbon conductive layer II or a portion of the surface of the straight portion is provided with the carbon conductive layer II.
[0048] In some embodiments of the present invention, the carbon conductive layer II includes a carbon conductive layer II-1 disposed on the surface of the curved portion and a carbon conductive layer II-2 disposed on the surface of the straight portion, wherein the carbon conductive layer II-1 and the carbon conductive layer II-2 are connected. Optionally, the area of the carbon conductive layer II-1 may be 1 / 10 to 1 of the area of the carbon conductive layer II, and may be 1 / 10 to 4 / 5.
[0049] In some embodiments of the present invention, the bend is arc-shaped, and the carbon conductive layer I-1 is located within the arc line where the bend is located.
[0050] According to the above embodiments, the electrode for detecting perfluoroalkyl and polyfluoroalkyl substances includes a working electrode, an auxiliary electrode, and a reference electrode. The working electrode is formed by a metal conductive layer I, a carbon conductive layer I, and a polymer layer II in conjunction with an insulating layer I. The auxiliary electrode is formed by a metal conductive layer II and a carbon conductive layer II in conjunction with an insulating layer II. The reference electrode is formed by a metal conductive layer III in conjunction with an insulating layer III. The working electrode contains a polymer layer II, which can interact with the analyte in the test solution. The auxiliary electrode assists in charge transfer or current flow throughout the electrode system and can form a circuit with the working electrode, ensuring smooth charge transfer between the electrodes. The reference electrode is used to measure the potential change of the working electrode.
[0051] In some embodiments of the present invention, the substrate includes at least one of ceramic, polymer material, glass, or circuit board. For example, ceramic sheets are selected as the ceramic. Using ceramic sheets, polymer materials, glass, or circuit boards as substrates has the characteristics of high mechanical strength. For example, ceramics have advantages such as stable chemical properties and good insulation performance.
[0052] In some embodiments of the present invention, the metal conductive layer I, the metal conductive layer II, and the metal conductive layer III all comprise metals, including but not limited to at least one of metals such as gold, silver, and copper.
[0053] In some embodiments of the present invention, the metal conductive layer I includes at least one of a silver conductive layer, a gold conductive layer, or a gold-silver alloy conductive layer; and / or, the metal conductive layer II includes at least one of a silver conductive layer, a gold conductive layer, or a gold-silver alloy conductive layer; and / or, the metal conductive layer III includes at least one of a silver conductive layer, a gold conductive layer, or a gold-silver alloy conductive layer.
[0054] In some embodiments of the present invention, the polymer layer II comprises a molecularly imprinted polymer (MIP).
[0055] Through the above-described embodiments, the MIP forms a specific cavity structure through the template molecule during preparation, thereby enabling selective recognition of target molecules corresponding to the template molecule. MIPs are low-cost to prepare, highly sensitive, selective, and chemically stable, maintaining high activity even under significant variations in parameters such as pH, temperature, and pressure. Therefore, they are widely used in chemical sensing, separation and purification, and biosensing. Furthermore, the structure of MIPs is easily tunable; by selecting suitable monomers and templates and polymerizing them, polymers with specific recognition functions for certain PFAS can be obtained.
[0056] In some embodiments of the present invention, the polymer contained in polymer layer II includes a conductive polymer.
[0057] In some embodiments of the present invention, the monomer includes at least one of aniline, o-phenylenediamine, dopamine, or pyrrole.
[0058] In some embodiments of the present invention, one end of the PFAS has an acidic functional group, and the hydrogen atoms on the carbon chain backbone are completely or partially substituted with fluorine.
[0059] In some embodiments of the present invention, the template molecule includes at least one selected from perfluorooctane sulfonate, a homologue of perfluorooctane sulfonate, perfluorooctanoic acid, a homologue of perfluorooctanoic acid, perfluorohexanoic acid, or potassium perfluorohexane sulfonate.
[0060] Among them, perfluorooctanoic acid, abbreviated as PFOA, CAS: 335-67-1;
[0061] In some embodiments of the present invention, the template molecule includes at least one of a perfluorooctane sulfonate compound or a homologue of a perfluorooctane sulfonate compound.
[0062] In some embodiments of the present invention, the perfluorooctane sulfonate compound includes potassium perfluorooctane sulfonate (PFOS, CAS: 2795-39-3).
[0063] In some embodiments of the present invention, in step S1, the raw materials for preparing the conductive metal layer I and / or conductive metal layer II and / or conductive metal layer III include conductive metal paste. Optionally, the conductive metal paste may be conductive silver paste, conductive gold paste, etc.
[0064] In some embodiments of the present invention, the conductive metal paste includes metal powder, binder I, filler I, and auxiliary material I.
[0065] Optionally, the metal powder, binder I, filler I, and auxiliary material I include, but are not limited to, the metal powder, binder, filler, and auxiliary material used in conductive silver pastes in the art, and may also be purchased from conventional markets or other commercial channels.
[0066] In some embodiments of the present invention, the binder I includes, but is not limited to, one or more of rosin, rubber, gum arabic, modified rosin, synthetic rubber and polyamide, phenolic resin, chlorinated polypropylene resin, polyaniline resin, etc.; and / or, the filler I includes, but is not limited to, one or more of terrazzo powder, barium sulfate, calcium carbonate, magnesium carbonate, etc.; and / or, the auxiliary material I includes, but is not limited to, one or more of plasticizers, leveling agents, etc., wherein the plasticizer may be, for example, di(2-ethylhexyl) phthalate (DEHP); the leveling agent includes, but is not limited to, one or more of polysiloxane, polyether, silicone resin, etc.
[0067] Optionally, the conductive metal paste further includes solvent I. Optionally, solvent I includes, but is not limited to, one or more of benzene, toluene, acetone, cyclohexanone, diethyl ether, and ethylene glycol methyl ether.
[0068] In some embodiments of the present invention, the conductive metal paste comprises, by weight parts: 17-30 parts of binder I, filler I, and auxiliary material I, 20-40 parts of metal powder, and 25-40 parts of solvent I. Optionally, the conductive metal paste comprises 20-40 wt% metal powder, 25-40 wt% solvent I, and 17-30 wt% binder I, filler I, and auxiliary material I.
[0069] In some embodiments of the present invention, the metal powder includes at least one of gold powder or silver powder.
[0070] In some embodiments of the present invention, in step S1, the raw materials for preparing the carbon conductive layer I and / or the carbon conductive layer II include conductive carbon paste.
[0071] In some embodiments of the present invention, the conductive carbon paste includes carbon powder, binder II, filler II, and auxiliary material II.
[0072] Optionally, the toner, binder II, filler II, and auxiliary material II include, but are not limited to, the toner, binder, filler, and auxiliary material used in conductive carbon pastes in the art, and may also be purchased from conventional markets or other commercial channels.
[0073] In some embodiments of the present invention, the binder II includes, but is not limited to, one or more of rosin, rubber, gum arabic, modified rosin, synthetic rubber and polyamide, phenolic resin, chlorinated polypropylene resin, polyaniline resin, etc.; and / or, the filler II includes, but is not limited to, one or more of terrazzo powder, barium sulfate, calcium carbonate, magnesium carbonate, etc.; and / or, the auxiliary material II includes, but is not limited to, one or more of plasticizers, leveling agents, etc., wherein the plasticizer may be, for example, di(2-ethylhexyl) phthalate (DEHP); the leveling agent includes, but is not limited to, one or more of polysiloxane, polyether, silicone resin, etc.
[0074] Optionally, the conductive carbon paste further includes solvent II. Optionally, solvent II includes, but is not limited to, one or more of benzene, toluene, acetone, cyclohexanone, diethyl ether, and ethylene glycol methyl ether.
[0075] In some embodiments of the present invention, the conductive carbon paste comprises, by weight parts: 17-30 parts of binder II, filler II, and auxiliary material II, 20-40 parts of carbon powder, and 25-40 parts of solvent II. Optionally, the conductive carbon paste comprises 20-40 wt% carbon powder, 25-40 wt% solvent II, and 17-30 wt% binder II, filler II, and auxiliary material II.
[0076] In some embodiments of the present invention, in step S1, the raw materials for preparing insulating layer I and / or insulating layer II and / or insulating layer III include insulating ink.
[0077] In some embodiments of the present invention, the insulating ink includes a colorant, a binder III, a filler III, and an auxiliary material III. Optionally, the colorant, binder III, filler III, and auxiliary material III include, but are not limited to, the colorants, binders, fillers, and auxiliary materials used in insulating inks in the art, and may also be commercially available from conventional markets.
[0078] In some embodiments of the present invention, the colorant includes, but is not limited to, one or more of phthalocyanine, Lithol Ruby Red BK, Acid Yellow, titanium dioxide, fluorescent pigments, gold / silver powder, carbon black, etc.; and / or, the binder III includes, but is not limited to, one or more of rosin, rubber, gum arabic, modified rosin, synthetic rubber and polyamide, phenolic resin, chlorinated polypropylene resin, polyaniline resin, etc.; and / or, the filler III includes, but is not limited to, one or more of terrazzo powder, barium sulfate, calcium carbonate, magnesium carbonate, etc.; and / or, the auxiliary material III includes, but is not limited to, one or more of plasticizers, leveling agents, etc., wherein the plasticizer may be, for example, di(2-ethylhexyl) phthalate (DEHP); the leveling agent includes, but is not limited to, one or more of polysiloxane, polyether, silicone resin, etc.
[0079] Optionally, the insulating ink further includes solvent III. Optionally, solvent III includes, but is not limited to, one or more of benzene, toluene, acetone, cyclohexanone, diethyl ether, and ethylene glycol methyl ether.
[0080] In some embodiments of the present invention, the insulating ink comprises, by weight parts: 17-30 parts of binder III, filler III, and auxiliary material III, 20-40 parts of colorant, and 25-40 parts of solvent III. Optionally, the insulating ink comprises 20-40 wt% pigment, 25-40 wt% solvent III, and 17-30 wt% binder III, filler III, and auxiliary material III.
[0081] In some embodiments of the present invention, the insulating ink includes a UV-curing insulating ink. Optionally, the UV-curing insulating ink includes, but is not limited to, ultraviolet-curing insulating inks.
[0082] In some embodiments of the present invention, the photocurable insulating ink includes reactive oligomers, active monomers, photoinitiators, colorants, and additives.
[0083] Optionally, the reactive oligomers (such as UV-polymerizable unsaturated resins), reactive monomers, photoinitiators, colorants, and additives include, but are not limited to, the reactive oligomers, photoinitiators, colorants, and additives used in insulating inks in the art, and may also be commercially available from conventional markets.
[0084] In some embodiments of the present invention, the photocurable insulating ink comprises, by weight percentage, 35-60% reactive oligomer, 15-50% active monomer, 3-7% photoinitiator, 10-30% colorant and 1-5% additive.
[0085] In some embodiments of the present invention, the reactive oligomer includes at least one of epoxy diacrylate, polyester diacrylate, or polyurethane diacrylate; and / or, the reactive monomer includes at least one of tripropylene glycol diacrylate and hexanediol diacrylate; and / or, the photoinitiator includes at least one of benzophenone, thioxanthone, and benzoin ether; and / or, the colorant includes, but is not limited to, at least one of phthalocyanine, titanium dioxide, fluorescent pigments, gold / silver powder, and carbon black; and / or, the additive includes, but is not limited to, one or more of the binder III, filler III, and auxiliary material III. Optionally, the additive includes microcrystalline wax.
[0086] In some embodiments of the present invention, in step S1-1, conductive metal paste is coated onto the surface of the substrate and dried to prepare conductive metal layers I to III, thereby obtaining a substrate containing conductive metal layers; optionally, the drying temperature is selected from 90-150°C; then conductive carbon paste is coated onto the surface of conductive metal layer I and / or the surface of the substrate and the surface of conductive metal layer II, and dried to obtain conductive carbon layer I and conductive carbon layer II, respectively; optionally, the drying temperature is selected from 90-150°C.
[0087] In some embodiments of the present invention, in steps S1-2, insulating ink is applied to the surfaces of metal conductive layer I, metal conductive layer II, and metal conductive layer III, and dried to form insulating layer I, insulating layer II, and insulating layer III respectively, thereby obtaining a substrate with intermediate electrode group I on the surface; optionally, the drying temperature is selected from 90-150°C.
[0088] In some embodiments of the present invention, the method of applying conductive metal paste includes screen printing conductive metal paste; and / or, the method of applying conductive carbon paste includes screen printing conductive carbon paste; and / or, the method of applying insulating ink includes screen printing insulating ink.
[0089] In some embodiments of the present invention, after applying insulating ink, it is cured under ultraviolet light to form the insulating layers I to III.
[0090] In some embodiments of the present invention, in step S2, the activation time is selected from 0.5-10 min, and can be selected from 1-7 min.
[0091] In some embodiments of the present invention, in step S2, the power of the activation treatment is selected from 0.01-150W, and can be selected from 0.01-100W.
[0092] In some embodiments of the present invention, step S3 includes: obtaining the polymer layer by electropolymerization on the surface of the activated carbon conductive layer I in an electropolymerization solution containing template molecules and monomers.
[0093] In some embodiments of the present invention, the molar ratio of template molecules to monomers in the electropolymerization solution includes 1:(5-20), and may be selected as 1:(9-11).
[0094] In some embodiments of the present invention, the concentration of template molecules in the electropolymerization solution is selected from 0.1-10 mmol / L, and may be 0.5-3 mmol / L.
[0095] In some embodiments of the present invention, the concentration of monomer in the electropolymerization solution is selected from 1-100 mmol / L, and may be 5-30 mmol / L.
[0096] In some embodiments of the present invention, the electropolymerization solution further includes solvent I and a buffer solution.
[0097] In some embodiments of the present invention, solvent I includes at least one of methanol, ethanol, isopropanol, acetone or toluene.
[0098] In some embodiments of the present invention, the buffer solution includes at least one of acetate-sodium acetate buffer or phosphate buffer.
[0099] In some embodiments of the present invention, the pH of the phosphate buffer is approximately 7.4.
[0100] In some embodiments of the present invention, the concentration of acetate-sodium acetate in the acetate-sodium acetate buffer is selected from 0.05-0.3 mol / L; and / or, the pH of the acetate-sodium acetate buffer is selected from 5.75-5.9.
[0101] In some embodiments of the present invention, the volume ratio of solvent I to the buffer solution is selected from 1:(0.5-5); or optionally 1:(1-3).
[0102] In some embodiments of the present invention, in step S3, electropolymerization is performed using cyclic voltammetry; optionally, the potential range is 0-1V, and / or the scan rate is 20-100mV / s, and / or the number of cycles is 10-25. Optionally, the scan rate is 50mV / s.
[0103] In some embodiments of the present invention, the template molecule removal step S3 specifically includes placing the electrode after obtaining polymer layer I in a mixture of methanol and water, and then in methanol to remove the template molecules, thereby obtaining polymer layer II. Optionally, the volume ratio of methanol to water in the mixture is selected from 1:(0.2-5), specifically 1:1, etc.
[0104] In some embodiments of the present invention, in step S3, which involves removing template molecules, the electrode after obtaining polymer layer I is placed in a mixture of methanol and water for 10-50 min, and then placed in methanol for 0.2-5 min.
[0105] In some embodiments of the present invention, in step S3, after removing the template molecules, the electrode after obtaining polymer layer I is placed in a mixture of methanol and water for 15-25 min, and then placed in methanol for 0.5-2 min.
[0106] In some embodiments of the present invention, the thickness of the substrate is selected from 0.3-0.8 mm.
[0107] In some embodiments of the present invention, the thickness of the metal conductive layer I is selected from 0.02-0.2 mm; and / or, the thickness of the metal conductive layer II is selected from 0.02-0.2 mm; and / or, the thickness of the metal conductive layer III is selected from 0.02-0.2 mm.
[0108] In some embodiments of the present invention, the width of the metal conductive layer I is selected from 0.5-1.5 mm; and / or, the width of the metal conductive layer II is selected from 0.5-1.5 mm; and / or, the width of the metal conductive layer III is selected from 0.5-1.5 mm.
[0109] In some embodiments of the present invention, the length of the metal conductive layer I is selected from 5-30 mm; and / or, the length of the metal conductive layer II is selected from 5-40 mm; and / or, the length of the metal conductive layer III is selected from 5-30 mm.
[0110] In some embodiments of the present invention, the area of the metal conductive layer I is selected from 0.02-1 cm². 2 ; and / or, the area of the metal conductive layer II is selected from 0.02-1 cm². 2 ; and / or, the area of the metallic conductive layer III is selected from 0.02-1 cm². 2 .
[0111] In some embodiments of the present invention, the thickness of the carbon conductive layer I is selected from 0.02-0.2 mm; and / or, the thickness of the carbon conductive layer II is selected from 0.02-0.2 mm.
[0112] In some embodiments of the present invention, the area of the carbon conductive layer I is selected from 0.001-1 cm². 2 ; and / or, the area of the carbon conductive layer II is selected from 0.001-1 cm². 2 .
[0113] In some embodiments of the present invention, the thickness of insulating layer I is selected from 0.01-0.05 mm; and / or, the thickness of insulating layer II is selected from 0.01-0.05 mm; and / or, the thickness of insulating layer III is selected from 0.01-0.05 mm.
[0114] In some embodiments of the present invention, the thickness of polymer layer I is selected from 0.05-0.2 μm; and / or, the area of polymer layer I is selected from 0.001-1 cm². 2 .
[0115] In some embodiments of the present invention, the thickness of the polymer layer II is selected from 0.05-0.2 μm.
[0116] In some embodiments of the present invention, the area of the polymer layer II is selected from 0.001-1 cm². 2 .
[0117] In some embodiments of the present invention, the length of the screen-printed electrode is selected from 20-50 mm.
[0118] In some embodiments of the present invention, the width of the screen-printed electrode is selected from 5-10 mm.
[0119] In a second aspect, the present invention provides an electrode for the detection of perfluoroalkyl and polyfluoroalkyl substances, which is prepared by the above-described method.
[0120] In some embodiments of the present invention, the electrode used for detecting perfluoroalkyl and polyfluoroalkyl substances is a screen-printed electrode.
[0121] In some embodiments of the present invention, the screen-printed electrode includes a substrate and a working electrode, a reference electrode, and an auxiliary electrode disposed on the substrate.
[0122] In some embodiments of the present invention, the working electrode includes a metal conductive layer I, a carbon conductive layer I, and a polymer layer II, wherein the metal conductive layer I is disposed on the surface of the substrate; the carbon conductive layer I is partially or entirely located on the surface of the metal conductive layer I, or the entire carbon conductive layer I is located on the surface of the substrate; and the polymer layer II is disposed on the surface of the carbon conductive layer I. Optionally, a portion of the carbon conductive layer I is located on the surface of the metal conductive layer I, and another portion is located on the surface of the substrate.
[0123] In some embodiments of the present invention, the auxiliary electrode includes a metal conductive layer II and a carbon conductive layer II stacked on the surface of the substrate.
[0124] In some embodiments of the present invention, the reference electrode includes a metal conductive layer III disposed on the surface of the substrate.
[0125] A third aspect of the present invention provides an electrochemical sensor comprising the electrode described above for the detection of perfluoroalkyl and polyfluoroalkyl substances.
[0126] The electrochemical sensor according to embodiments of the present invention has at least the following beneficial effects:
[0127] The electrochemical sensor used in this invention for detecting PFAS features high sensitivity, good selectivity, low detection cost, and simple operation. This electrochemical sensor is also easily miniaturized and integrated, showing great promise for future development. The electrode used (for the detection of perfluoroalkyl and polyfluoroalkyl substances) is a miniaturized three-electrode system, offering advantages such as small size, low cost, ease of fabrication, mass production capability, and easily tunable structure. Detection can be completed with only a small amount of sample, and it can be carried to different scenarios, facilitating rapid real-time monitoring of PFAS.
[0128] In a fourth aspect, the present invention provides a method for detecting PFAS, comprising the following steps: using the electrode described above for detecting perfluoroalkyl and polyfluoroalkyl substances, and employing an electrochemical detection method to detect PFAS.
[0129] The detection method for PFAS according to embodiments of the present invention has at least the following beneficial effects:
[0130] This invention utilizes an electrode for the detection of perfluoroalkyl and polyfluoroalkyl substances, based on electrochemical detection technology, to achieve direct detection of PFAS in environmental samples without pre-concentration. It has the advantages of high sensitivity, low cost, portability, and on-site detection capability.
[0131] In some embodiments of the present invention, the electrochemical techniques used for electrochemical detection include CV (cyclic voltammetry), DPV (differential pulse voltammetry), or it (chronoamperometry), etc.
[0132] In some embodiments of the present invention, the electrode is placed in an electrochemical detection reagent for electrochemical detection. The target analyte can be detected based on the magnitude of the redox current. The electrochemical detection reagent includes potassium chloride, ferroceneformic acid, potassium ferricyanide, or ferrocene methanol, etc.
[0133] In some embodiments of the present invention, the electrochemical detection reagent comprises an aqueous solution containing K3[Fe(CN)6] / K4[Fe(CN)6] and KCl. Optionally, the concentration of K3[Fe(CN)6] / K4[Fe(CN)6] in the aqueous solution is 0.1-10 mmol / L.
[0134] In some embodiments of the present invention, the concentration of KCl in the aqueous solution includes 0.05-0.3 mol / L.
[0135] In some embodiments of the present invention, the detection limit of PFAS in the detection method includes (2-5)×10⁻⁶. -12 g / L, for example, could be 3.498 × 10 -12 g / L, approximately 0.003498ppt.
[0136] Through the above embodiments, the detection method of the present invention has high sensitivity, is more suitable for the trace detection of PFAS, and has strong detection capability.
[0137] In some embodiments of the present invention, the detection method exhibits a linear relationship in the range of 0.01-0.5 pmol / L, and / or, in the range of 0.5 pmol / L-5 nmol / L.
[0138] Through the above embodiments, the detection method of the present invention exhibits a wide linear range for PFAS, that is, a linear relationship within the range of 0.01-5000 pmol / L, spanning 5 × 10⁻⁶ pmol / L. 5 It can be used to detect PFAS in a wide range of concentrations in water, soil and air, and has good application prospects.
[0139] In some embodiments of the present invention, the detection concentration range of PFAS in the detection method includes 0.01 pmol / L to 100 nmol / L.
[0140] In a fifth aspect, the present invention proposes the application of the above-described electrode and electrochemical sensor in the detection of PFAS in water. Attached Figure Description
[0141] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0142] Figure 1 This is a schematic diagram of the preparation process of intermediate electrode I in Embodiment 1 of the present invention;
[0143] Figure 2 This is a schematic diagram of the preparation process of the electrode polymer layer in Example 1 of the present invention;
[0144] Figure 3 This is a schematic diagram of the SPE electrode used for PFAS detection in Embodiment 1 of the present invention;
[0145] Figure 4 The above are the CV curves of intermediate electrode I before activation and intermediate electrode II after activation in Examples 1-2 of the present invention.
[0146] Figure 5 This is a comparison diagram of the redox peak potential difference and peak current of intermediate electrode I before activation and intermediate electrode II after activation in Examples 1-2 of the present invention;
[0147] Figure 6 This is a CV curve diagram of intermediate electrode I before activation and intermediate electrode II after activation in Example 3 of the present invention;
[0148] Figure 7 This is a comparison diagram of the redox peak potential difference and peak current of intermediate electrode I before activation and intermediate electrode II after activation in Example 3 of the present invention;
[0149] Figure 8 This is a graph showing the relationship between the peak current of the SPE electrode and the PFOS concentration in Example 1 of the present invention.
[0150] Figure 9 This is a DPV response diagram of PFOS at various concentrations using an SPE electrode in Example 1 of the present invention;
[0151] Figure 10 This is a linear relationship graph of the PFOS response using the SPE electrode in Embodiment 1 of the present invention;
[0152] Figure 11 This is a graph showing the PFAS selectivity test results using an SPE electrode in Embodiment 1 of the present invention.
[0153] Figure 12 This is an infographic showing the use of mineral water in the experimental examples of this invention;
[0154] Figure 13 This is a map showing the geographical location of the river and lake water intake points used in the experimental examples of this invention. Detailed Implementation
[0155] The following will describe the concept and technical effects of the present invention clearly and completely with reference to embodiments, so as to fully understand the purpose, features and effects of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.
[0156] Unless otherwise specified, the experimental methods described in the following examples are generally performed under conventional conditions in the art or as recommended by the manufacturer; the raw materials and reagents used are all commercially available from the conventional market unless otherwise specified.
[0157] Conductive silver paste: by weight, it includes 20-40 parts silver powder, 25-40 parts solvent I, and 17-30 parts binder I, filler I and auxiliary material I; it can also be purchased from conductive silver paste sold in the conventional market.
[0158] Conductive carbon paste: by weight, it includes 17-30 parts of binder II, filler II and auxiliary material II, 20-40 parts of carbon powder, and 25-40 parts of solvent II; conductive carbon paste can also be purchased from the conventional market.
[0159] Wherein, binder I and binder II are independently selected from at least one of rosin, rubber, gum arabic, modified rosin, synthetic rubber and polyamide, phenolic resin, chlorinated polypropylene resin or polyaniline resin; filler I and filler II are independently selected from at least one of terrazzo powder, barium sulfate, calcium carbonate or magnesium carbonate; auxiliary material I and auxiliary material II include at least one of di(2-ethylhexyl) phthalate and leveling agent (polysiloxane, polyether or silicone resin); solvent I and solvent II are independently selected from at least one of benzene, toluene, acetone, cyclohexanone, diethyl ether or ethylene glycol methyl ether;
[0160] Light-curing insulating inks: By weight percentage, they consist of 35-60% reactive oligomers, 15-50% active monomers, 3-7% photoinitiators, 10-30% colorants, and 1-5% additives. Light-curing insulating inks are also available from the general market.
[0161] The reactive oligomer is at least one of epoxy diacrylate, polyester diacrylate or polyurethane diacrylate; the active monomer is tripropylene glycol diacrylate and / or hexanediol diacrylate; the photoinitiator is benzophenone and / or thioxanthone and / or benzoin ether; the colorant is phthalocyanine (or titanium dioxide, fluorescent pigment); and the additive is microcrystalline wax.
[0162] In the screen printing process: the screen printing plate used has a mesh count of 400, but the mesh count can also be other, such as 300-500.
[0163] Example 1
[0164] This embodiment discloses an SPE electrode for PFAS detection, the preparation process of which specifically includes:
[0165] (I) Preparation of intermediate electrode assembly I, the preparation process is shown in the schematic diagram below. Figure 1 As shown, it includes: using a blank ceramic plate (comprising 3 rows of 13 small grids, totaling 39 pieces, each approximately 8mm wide and 30mm long) as a substrate, and screen printing a silver conductive layer onto the substrate surface using conductive silver paste as the raw material (3 silver conductive layers are printed on each substrate surface, such as...). Figure 1 As shown in (a), from left to right, the layers are silver conductive layer II, silver conductive layer I, and silver conductive layer III, dried at 120°C for 10 minutes. Using conductive carbon paste as raw material, carbon conductive layer I and carbon conductive layer II are screen-printed onto the surface of silver conductive layer I and / or the substrate, and onto the surface of silver conductive layer II, respectively, and dried at 120°C for 10 minutes. Carbon conductive layer I and carbon conductive layer II are located on the same side of the substrate surface. A portion of carbon conductive layer I is located on the surface of silver conductive layer I (e.g., ...). Figure 1 As shown in region A (d), it is strip-shaped, also known as carbon conductive layer I-2), and another part (as shown in...) Figure 1 As shown in region B (d), the circular layer (also called carbon conductive layer I-1) is in direct contact with the substrate surface, or it can be entirely located on the surface of silver conductive layer I or the substrate surface, with carbon conductive layer I in contact with silver conductive layer I. Optionally, silver conductive layer II includes a straight portion and a curved portion connected to the straight portion. The curved portion surface is provided with carbon conductive layer II, and a portion of the straight portion surface is also provided with carbon conductive layer II. Optionally, the curved portion is arc-shaped, and the circular portion of carbon conductive layer I is located within the arc line of the curved portion.
[0166] The substrate surface is composed of regions one, two, and three, as follows: Figure 1 As shown in (b), region one is a sector approximately 5 / 6 of a circle (radius approximately 3.25 mm), and the area of region one is 0.28 cm². 2 (The area of region one is 0.15-0.5 cm²) 2(Any of these are acceptable); the area of region three can be 1 / 20 to 1 / 2 of the total area of the substrate surface; carbon conductive layer I and carbon conductive layer II are all located in region one (or both carbon conductive layer I and carbon conductive layer II are partially located in region one); using photocurable insulating ink as raw material, an insulating layer (including the silver conductive layer located in region two and the substrate surface printed with the photocurable insulating ink) is screen printed in region two, and treated with 3000W, 365nm UV for 30 seconds (UV curing) to obtain intermediate electrode group I (the formed insulating layer includes insulating layers I to III located on the surfaces of silver conductive layers I to III respectively).
[0167] In intermediate electrode group I, the ceramic plate is approximately 0.5 mm thick; each silver conductive layer is approximately 0.1 mm thick (thickness can be 0.02-0.2 mm), 1-1.3 mm wide, and can be longer than 8 mm; each carbon conductive layer is approximately 0.1 mm thick (thickness can be 0.02-0.2 mm); the carbon conductive layer II is 1-1.3 mm wide; the circular portion of carbon conductive layer I that is in direct contact with the substrate has a diameter of approximately 3 mm; the portion of carbon conductive layer I located on the surface of silver conductive layer I has a width of 1-1.3 mm and a length of approximately 3 mm; the insulating layer is approximately 0.02 mm thick (thickness can be 0.01-0.05 mm); more specifically:
[0168] The area of the silver conductive layer I can be 0.22 cm². 2 The area of the straight portion of the silver conductive layer II can be 0.22 cm². 2 The area of the bend in the silver conductive layer II can be 0.086 cm². 2 The area of the silver conductive layer III can be 0.231 cm². 2 (The area within region one can be 0.001-0.03 cm²) 2 For example, it can be 0.011cm 2 );
[0169] The area of carbon conductive layer I-1 in carbon conductive layer I is 0.071 cm². 2 The area of carbon conductive layer I-2 can be 0.033 cm². 2 The straight section area of carbon conductive layer II can be 0.033 cm². 2 The area of the bend can be 0.086 cm². 2 Insulation layers I-III are parallel to each other, with the same length and width, and each can have an area of 0.187 cm². 2 .
[0170] (II) Activation treatment: The intermediate electrode group I obtained in step (I) was pretreated using a Plasma cleaner, including: oxygen partial pressure of 0.2 MPa, oxygen flow time of 5 minutes, frequency of 80 kHz, and vacuuming time of 1 minute. The Plasma power was 80 W for 3 minutes to obtain intermediate electrode group II.
[0171] (III) Preparation of the polymer layer (sensitive membrane, thickness 0.05-0.2 μm is acceptable): A specific recognition membrane (MIP membrane) is modified on the surface of the carbon conductive layer I in the intermediate electrode group II by electropolymerization using PFOS (potassium perfluorooctyl sulfonate) as a template. The preparation process is shown in the schematic diagram below. Figure 2 As shown, a MIP film was prepared on the electrode surface using o-phenylenediamine (o-PD) monomer as raw material (green square) and PFOS (yellow triangle) as template. Since the cavity formed by the template in the MIP film has the same structure as the PFOS to be measured, ... Figure 2 As shown, only the PFOS shown in the figure can bind most tightly to these cavities. Other PFAS structures, such as potassium perfluorohexanesulfonate and perfluorooctanoic acid (PFOA), differ from the PFOS in this example and therefore cannot bind tightly to the cavities. Potassium perfluorohexanesulfonate also has a sulfonyl functional group at one end, but its carbon chain length is 6 carbons, while PFOS has 8 carbons; the carbon chain length of PFOA is 8 carbons, but its functional group at one end is a carboxyl group instead of a sulfonyl group, which is different from the group type of PFOS. Besides structural correspondence, the F atoms of PFAS interact with the groups within the cavities via hydrogen bonds. Therefore, the sensitive membrane prepared using PFOS as a template binds most tightly to PFOS.
[0172] The preparation of the polymer layer (sensitive membrane) specifically includes:
[0173] Prepare an electropolymerization solution; in the electropolymerization solution, the molar ratio of template molecule (PFOS) to functional monomer (o-phenylenediamine o-PD) is 1:10 (the concentration of template molecule in the electropolymerization solution is 1 mmol / L), the concentration of acetate-sodium acetate buffer is 0.1 mol / L, the pH is 5.75-5.9, and the volume ratio of methanol to buffer is 1:2.
[0174] The carbon conductive layer I of the intermediate electrode group II was placed in the electropolymerization solution, and electropolymerization was carried out by cyclic voltammetry with a potential range of 0 to 1 V and a scan rate of 50 mV / s. After 10 cycles, a MIP film containing a PFOS template was obtained on the surface of the carbon conductive layer I (the circular carbon conductive layer surface of the intermediate electrode group II).
[0175] The prepared electrode was first immersed in a methanol-water (1:1, v / v) solution for 20 minutes, and then immersed in methanol for 40-50 seconds to remove template molecules, thus obtaining the SPE electrode for PFAS detection. The resulting SPE electrode for PFAS detection exhibits a specific response to PFAS (especially PFOS).
[0176] Optionally, in the electropolymerization step, region one of the intermediate electrode group II can be placed in the electropolymerization solution, and the direction of CV scanning can be controlled based on cyclic voltammetry to oxidize o-PD and generate Po-PD on the surface of carbon conductive layer I.
[0177] The SPE electrode for PFAS detection prepared in this embodiment is shown in the schematic diagram below. Figure 3 As shown, Figure 3 The right-hand diagram shows the working electrode, reference electrode, and auxiliary electrode contained in region one of the SPE electrodes (parts located in regions two and three are not shown).
[0178] This embodiment also discloses an electrochemical sensor, including the SPE electrode for PFAS detection prepared in this embodiment.
[0179] This embodiment also discloses a method for detecting PFAS. Using the SPE electrode for PFAS detection prepared in this embodiment, PFAS is detected by an electrochemical detection method. The electrochemical techniques used in the electrochemical detection include CV, DPV (differential pulse voltammetry), or it (chronoamperometry).
[0180] In this invention, the dimensions of each layer can be adjusted as needed.
[0181] Example 2
[0182] This embodiment discloses a series of SPE electrodes for PFAS detection. The only difference between this embodiment and Embodiment 1 is that in step (II) activation treatment, the power and duration of the Plasma are 20-100W and 3min, respectively.
[0183] This embodiment also discloses a series of electrochemical sensors, including the SPE electrode for PFAS detection prepared in this embodiment.
[0184] This embodiment also discloses a method for detecting PFAS. Using the SPE electrode for PFAS detection prepared in this embodiment, PFAS is detected by an electrochemical detection method. The electrochemical techniques used in the electrochemical detection include CV, DPV (differential pulse voltammetry), or it (chronoamperometry).
[0185] Example 3
[0186] This embodiment discloses a series of SPE electrodes for PFAS detection. The only difference between this embodiment and Embodiment 1 is that in step (II) activation treatment, the power and duration of the Plasma are 80W and 0-7min, respectively.
[0187] This embodiment also discloses a series of electrochemical sensors, including the SPE electrode for PFAS detection prepared in this embodiment.
[0188] This embodiment also discloses a method for detecting PFAS. Using the SPE electrode for PFAS detection prepared in this embodiment, PFAS is detected by an electrochemical detection method. The electrochemical techniques used in the electrochemical detection include CV, DPV (differential pulse voltammetry), or it (chronoamperometry).
[0189] Test case
[0190] This experimental example tested the intermediate electrode group II and the SPE electrode used for PFAS detection in the examples. Specifically, the SPE electrode was connected to the detector via an adapter, and the detector was controlled by software using a desktop computer / laptop / mobile phone. The detector is small in size and lightweight, making it easy to carry and thus enabling portable detection. This experimental example used a PalmSens4 electrochemical workstation.
[0191] (1) CV curve tests were performed on intermediate electrode group I before activation and intermediate electrode group II after activation in Examples 1-2. The test results are as follows: Figure 4 As shown, the specific test method includes: testing the CV curve of the electrode in a 0.1M KCl + 2mM K3[Fe(CN)6] / K4[Fe(CN)6] aqueous solution. The CV test conditions include: potential range: -0.3V to 0.7V, scan rate: 50mV / s, number of cycles: 1-4.
[0192] Figure 4 In the figure, the black curve is the CV curve of the SPE electrode without Plasma treatment, which is the intermediate electrode group I in Example 1; the Plasma duration of the intermediate electrode group II corresponding to all other curves is 3 minutes, and the Plasma treatment power of the intermediate electrode group II corresponding to each curve is as follows: purple curve is 100W, green curve is 80W, blue curve is 50W, and red curve is 20W.
[0193] By comparing the redox peak potential difference and the oxidation peak current, it can be seen that the SPE electrode treated with 80W for 3min exhibits a higher peak current and a smaller redox potential difference. If the power is further increased or the treatment time extended under these conditions, the peak current value no longer increases significantly, and the redox potential difference no longer decreases significantly. Therefore, 80W for 3min is the optimal pretreatment process. The comparison of the redox peak potential difference and peak current between intermediate electrode group I before activation and intermediate electrode group II after activation in Examples 1-2 is shown in the figure below. Figure 5 As shown.
[0194] The same test method described above was used to perform CV curve tests on intermediate electrode group I before activation and intermediate electrode group II after activation in Example 3. The test results are as follows: Figure 6 The relationship between peak CV current, interpeak potential difference, and activation treatment time is as follows: Figure 7 As shown:
[0195] Figure 6 In the figure, the black curve is the CV curve of the SPE electrode (intermediate electrode group I) without Plasma treatment; the other curves are the CV curves of the SPE electrode (intermediate electrode group II) treated with Plasma: the Plasma treatment power is 80W, the red curve is the CV curve after 1 minute of Plasma treatment, the blue curve is the CV curve after 3 minutes of Plasma treatment, the green curve is the CV curve after 5 minutes of Plasma treatment, and the purple curve is the CV curve after 7 minutes of Plasma treatment.
[0196] (2) Used for PFAS detection:
[0197] ① Feasibility Test: The SPE electrode prepared in Example 1 for PFAS detection was sequentially exposed to 0 (pure water), 100 pM PFOS incubation solution, and 500 pM PFOS incubation solution for 14-16 minutes. The current response of the SPE electrode was then tested sequentially using DPV (differential pulse voltammetry) in a 0.1 M KCl + 2 mM K3[Fe(CN)6] / K4[Fe(CN)6] aqueous solution. The DPV potential range was -0.2 V to 0.6 V, with a potential increment of 0.004 V, an amplitude of 0.02-0.03 V, a pulse width of 0.02-0.03 s, and a pulse period of 0.15-0.25 s. At least three SPE electrodes were used for this test, and each SPE electrode was tested at least three times at each concentration. The solvent for the incubation solution was water.
[0198] The results showed that the peak current decreased with increasing PFOS concentration, such as... Figure 8 : Figure 8The black curve represents the response of the SPE electrode to 0% PFOS (i.e., pure H2O), the red curve represents the response of the SPE electrode to 100 pM PFOS, and the blue curve represents the response of the SPE electrode to 500 pM PFOS. This demonstrates the feasibility of modifying the MIP membrane on the SPE surface using electropolymerization for PFOS detection. Specifically, the SPE electrode is immersed in a water sample for incubation. PFOS molecules in the water sample will specifically bind to the sensitive membrane (MIP membrane), changing the surface state of the electrode and causing a change in the electrochemical signal. The principle includes: PFAS (such as PFOS in this example) are electrochemically inert substances and do not easily undergo redox reactions on the electrode surface; when specific cavities on the MIP membrane surface are not bound to PFAS, the current peak measured by the SPE electrode is the largest. If PFAS binds to the cavities, the contact area between the MIP membrane and the solution decreases, and the resistance of the MIP membrane-solution interface increases, resulting in a decrease in the current peak.
[0199] ② Linearity test and detection limit calculation: The current response of the prepared SPE electrode was tested after exposing it to a blank incubation solution without PFAS. Then, the SPE electrode was sequentially exposed to incubation solutions containing different concentrations (from low to high) of PFAS and the current response was tested. Finally, a linear relationship between the electrode peak current value and the PFAS concentration was obtained, and the detection limit was calculated. The calibration curve was plotted with the average value and standard deviation of the peak current of the SPE electrode to each concentration of PFAS as the ordinate and the PFAS concentration represented by log10 as the abscissa. The detection limit was calculated based on LOD = 3s / m, where s represents the standard deviation of the peak current of the SPE electrode when the PFAS concentration is 0, and m represents the slope of the first segment of the calibration curve, in μA / pM.
[0200] Specifically, this includes: using the method described in ①, exposing the SPE electrode for PFAS detection prepared in Example 1 to pure water and PFOS incubation solutions of different concentrations, and then testing the current response of the SPE electrode to various concentrations of PFOS in a 0.1M KCl + 2mM K3[Fe(CN)6] / K4[Fe(CN)6] aqueous solution. The peak current was found to decrease with increasing PFOS concentration (e.g., ...). Figure 9 ). Figure 9In the diagram, the top black curve represents the SPE electrode's response to 0 pM PFOS (pure H2O), as indicated by the downward arrow. The electrode current decreases with increasing PFOS concentration. Besides 0 pM, the top red curve represents the SPE electrode's response to 0.01 pM PFOS, followed by curves representing the responses to 0.02 pM PFOS, 0.05 pM PFOS, 0.1 pM PFOS, 0.2 pM PFOS, 0.5 pM PFOS, 2 pM PFOS, 10 pM PFOS, 50 pM PFOS, 200 pM PFOS, 1000 pM PFOS, and 5000 pM PFOS.
[0201] Under the above test conditions, the peak current of the SPE electrode exhibits a good linear relationship with the PFOS concentration in the range of 0.01 pM to 5 nM, with a detection limit of 6.5 fM, or 6.5 × 10⁻⁶. -15 M. Since the molar mass of PFOS is 538.22 g / mol, the mass concentration of LOD is 3.498 × 10⁻⁶. -12 g / L or 0.003498 ppt. In the 0.01 pM to 0.5 pM range, the linear equation for peak current versus PFOS concentration is ip = -1.224lg c(PFOS) + 3.595, R 2 =0.998, in the range of 0.5 pM to 5 nM, the linear equation for peak current versus PFOS concentration is ip = -0.466lg c(PFOS) + 3.421, R 2 =0.932 (e.g.) Figure 10 ).
[0202] ③Selectivity: First, the prepared SPE electrode was exposed to a blank incubation solution and the current response was tested. Then, it was exposed to PFAS incubation solution and PFAS-interferant coexisting incubation solution respectively and the current response of the SPE electrode was tested. The difference between the two groups of electrode responses relative to the blank incubation solution group was compared.
[0203] The selectivity was tested using PFOA, PFHxA, PFHxS, NaCl, and HA as interfering substances. Among them, PFHxA: perfluorohexanoic acid, CAS: 307-24-4, a homologue of perfluorooctanoic acid (PFOA); PFHxS: potassium tridecylfluorohexanesulfonate, CAS: 3871-99-6, a homologue of PFOS (potassium perfluorooctyl sulfonate); HA: humic acid, CAS: 1415-93-6.
[0204] Specifically, it includes:
[0205] 1) Prepare six incubation solutions: 1 nM PFOS, 1 nM PFOS + 1 nM PFOA, 1 nM PFOS + 1 nM PFHxS, 1 nM PFOS + 1 nM PFHxA, 1 nM PFOS + 1 mM NaCl, and 1 nM PFOS + 1 ppm HA. Water is the solvent for all incubation solutions.
[0206] 2) The SPE electrode for PFAS detection prepared in Example 1 was exposed in the above 6 groups of incubation solutions (method as in ①), with 3 to 6 SPE electrodes used for exposure in each group;
[0207] 3) Testing the DPV (differential pulse voltammetry) response of the SPE electrode after exposure: The specific method is the same as described in ①. Peak currents were read, and the percentage decrease in peak current for each group was calculated based on the DPV peak current of the SPE electrode in the blank incubation solution (pure water). Finally, the degree of interference to the SPE in the remaining 5 groups was measured based on the percentage decrease in the DPV peak current of the SPE electrode in 1 nM PFOS. The results show that even with the coexistence of PFOS and interfering substances, the SPE electrode still possesses good specificity for PFOS (e.g., ...). Figure 11 ).
[0208] ④ Precision of the evaluation method: Using the SPE electrode for PFAS detection prepared in Example 1, the average peak current and standard deviation of DPV or CV corresponding to various PFOS concentrations, including 0 concentration, were calculated. The relative standard deviation (RSD) was obtained by dividing the RSD by the average and multiplying by 100%, which represents the stability and precision of the MIP-modified SPE electrode at each concentration. In the low concentration range (PFOS concentration between 0.01 pM and 0.5 pM), the RSD of the MIP-modified SPE electrode's response to PFOS was less than 5%, indicating that the SPE electrode prepared in this invention has high precision and can be used for the quantitative detection of PFAS in actual water samples.
[0209] ⑤ Testing of actual water samples (see Table 1), including:
[0210] 1) Water sample collection and pretreatment: Bottled mineral water and tap water were not pretreated. River water and lake water were filtered three times with qualitative filter paper and then purified using a needle filter with a pore size of 0.22μm. The bottled mineral water was Jingtian Baishui Mountain mineral water; details of the brand, production batch, and composition are available in [link to relevant documentation]. Figure 12 The river and lake water were taken from the Dasha River and a lake on the campus of Southern University of Science and Technology. For details of the specific water intake points, please refer to [link / reference needed]. Figure 13 The red dot indicates the location of the water intake point. Figure 13 (Left image shows the specific water intake point for the river; right image shows the specific water intake point for the lake.)
[0211] 2) Solution preparation: Using the 1 nM PFOS incubation solution in ③ as the stock solution, prepare 100 pM and 10 pM PFOS mineral water solutions sequentially with bottled mineral water, prepare 100 pM and 10 pM PFOS tap water solutions sequentially with tap water, prepare 100 pM and 10 pM PFOS river water solutions sequentially with purified river water, and prepare 100 pM and 10 pM PFOS lake water solutions sequentially with purified lake water.
[0212] 3) Detection of PFOS in bottled mineral water: The SPE electrode for PFAS detection prepared in Example 1 was sequentially exposed to mineral water solutions with 0 pM PFOS, 10 pM PFOS, and 100 pM PFOS, and DPV was measured sequentially (method as ①).
[0213] The accuracy of the measurement results was evaluated using the linear relationship between the peak current and PFOS concentration obtained in step ②. Test results with a recovery rate of 90% to 110% were considered accurate.
[0214] 4) Detection of PFOS in tap water, lake water, and river water: The SPE electrode for PFAS detection prepared in Example 1 was used for detection. In the case of tap water, the SPE electrode was exposed to tap water solutions with 0 pM PFOS, 10 pM PFOS, and 100 pM PFOS in sequence. In the case of lake water, the SPE electrode was exposed to lake water solutions with 0 pM PFOS, 10 pM PFOS, and 100 pM PFOS (after purification) in sequence. In the case of river water, the SPE electrode was exposed to river water solutions with 0 pM PFOS, 10 pM PFOS, and 100 pM PFOS (after purification) in sequence. The remaining experimental conditions and the evaluation methods of the experimental results were the same as those in the case of bottled mineral water in 3). In four scenarios—bottled mineral water, tap water, lake water, and river water—the recovery rate of PFOS detection by the SPE electrode was 90% to 110%. Therefore, the MIP-modified SPE electrode (the SPE electrode for PFAS detection prepared in Example 1) can achieve accurate detection of PFOS in real-world situations.
[0215] Table 1. Determination of PFOS content in actual water samples using the standard addition method.
[0216]
[0217] The reliability of the method was verified by measuring the recovery rate of spiked samples. In four cases—mineral water, tap water, river water, and lake water—the recovery rates of the SPE electrode were all concentrated in the range of 95% to 105%, and the standard deviation of the recovery rate was less than 5%, indicating that the SPE electrode in this invention can accurately quantify PFAS in actual situations.
[0218] Furthermore, the SPE electrode of this invention is placed in an electrochemical detection reagent to detect the target analyte based on the magnitude of the redox current. Peak current values are obtained through manual or automatic fitting, and the peak current values of the SPE electrode's response to various concentrations of PFAS (such as PFOS in Examples 1-2) are compared. Electrochemical techniques include CV, DPV, and it, while electrochemical detection reagents include ferrocene carboxylic acid, potassium ferricyanide, and ferrocene methanol.
[0219] In summary, the screen-printed electrode of this invention consists of a three-electrode system comprising a working electrode, an auxiliary electrode, and a reference electrode. This invention uses ceramic sheets, polymer materials, glass, or circuit boards as substrates, sequentially printing a silver conductive layer, a carbon conductive layer, and an insulating layer on their surfaces. A MIP recognition layer is prepared using a simple electropolymerization technique, and quantitative detection of PFOS is achieved using electrochemical detection technology. This method features ultra-low detection limits, good detection accuracy and specificity, and enables rapid on-site detection of PFOS. Preferably, the ceramic substrate used in the SPE electrode of this invention also possesses advantages such as high mechanical strength and resistance to strong acids and alkalis.
[0220] The SPE electrode preparation method in this invention is simple and efficient, allowing for mass production (such as electrode intermediates and the final SPE electrode), and is low in cost. Therefore, the SPE electrode has advantages such as ease of preparation, simple structure, mass production capability, low cost per unit, stable chemical properties, and small sample volume required for detection. Furthermore, the small size of the SPE electrode highly integrates the three-electrode system, making it suitable for real-time detection of pollutants. It is also durable, disposable after single use, and eliminates the need for maintenance of the reference electrode.
[0221] It should be noted that, unless otherwise specified, "room temperature" or "normal temperature" in this article refers to approximately 25°C; and the word "approximately" in numerical values in this article means an error of ±2%.
[0222] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.
Claims
1. A method for preparing an electrode for detecting perfluoroalkyl and polyfluoroalkyl substances, characterized in that, Includes the following steps: S1, take a substrate with an intermediate electrode group I on its surface, wherein the intermediate electrode group I includes a working electrode preform I, and the working electrode preform I includes a metal conductive layer I and a carbon conductive layer I in contact with each other; S2, the intermediate electrode group I is activated by oxygen plasma technology to obtain intermediate electrode group II, wherein the working electrode preform I is activated to form working electrode preform II; S3, using raw materials containing template molecules and monomers, a polymer layer I is prepared on the surface of the working electrode preform II, the template molecules are removed to obtain polymer layer II, and thus the electrode for the detection of perfluoroalkyl and polyfluoroalkyl substances is obtained, wherein the template molecules include PFAS.
2. The method for preparing the electrode according to claim 1, characterized in that, The electrode used for detecting perfluoroalkyl and polyfluoroalkyl substances is a screen-printed electrode; the template molecule is the same as the target analyte; in the working electrode preform I: the metal conductive layer I is disposed on the surface of the substrate; In the working electrode preform I: a portion of the carbon conductive layer I is disposed on the surface of the metal conductive layer I, and another portion is disposed on the surface of the substrate; And / or, the carbon conductive layer I is entirely disposed on the surface of the metal conductive layer I; and / or, the carbon conductive layer I is entirely disposed on the surface of the substrate.
3. The method for preparing the electrode according to claim 1, characterized in that, The polymer layer II comprises a molecularly imprinted polymer; the monomer comprises at least one of aniline, o-phenylenediamine, dopamine, or pyrrole; the template molecule comprises at least one of perfluorooctane sulfonate, a homologue of perfluorooctane sulfonate, perfluorooctanoic acid, a homologue of perfluorooctanoic acid, perfluorohexanoic acid, or potassium perfluorohexane sulfonate.
4. The method for preparing the electrode according to claim 1, characterized in that, In step S2, the activation time is selected from 0.5-10 min; and / or, in step S2, the activation power is selected from 0.01-150 W.
5. The method for preparing the electrode according to claim 1, characterized in that, Step S3 includes: preparing polymer layer I by electropolymerization on the surface of the activated carbon conductive layer I in an electropolymerization solution containing template molecules and monomers; the molar ratio of template molecules to monomers in the electropolymerization solution is 1:(5-20); the electropolymerization solution also includes solvent I and buffer solution; solvent I includes at least one of methanol, ethanol, isopropanol, acetone or toluene; and / or, the buffer solution includes at least one of acetate-sodium acetate buffer or phosphate buffer; in step S3, electropolymerization is performed by cyclic voltammetry, wherein the potential range is 0-1 V, the scan rate is 20-100 mV / s, and the cycle is 10-25 times; the template molecule removal step in step S3 specifically includes placing the electrode after obtaining polymer layer I in a mixture of methanol and water, and then in methanol to remove template molecules, thereby obtaining polymer layer II.
6. An electrode for detecting perfluoroalkyl and polyfluoroalkyl substances, characterized in that, It is prepared by the preparation method described in any one of claims 1-5.
7. An electrochemical sensor, characterized in that, Includes the electrode for detecting perfluoroalkyl and polyfluoroalkyl substances as described in claim 6.
8. A method for detecting PFAS, characterized in that, The method includes the following steps: using the electrode for detecting perfluoroalkyl and polyfluoroalkyl substances as described in claim 6, and employing an electrochemical detection method to detect PFAS; wherein the detection limit for PFAS in the detection method includes (2-5) × 10⁻⁶. -12 g / L.
9. The PFAS detection method according to claim 8, characterized in that, In the detection method, PFAS exhibits a linear relationship in the range of 0.01-0.5 pmol / L, and / or, PFAS exhibits a linear relationship in the range of 0.5 pmol / L - 5 nmol / L.
10. The application of the electrode for detecting perfluoroalkyl and polyfluoroalkyl substances as described in claim 6 or the electrochemical sensor as described in claim 7 for the detection of PFAS in water.